Impacts des changements d'affectation des terres sur les stocks de carbone des unités de peuplement végétal ligneux en zone nord soudanienne : exemple de l'arrondissement de Djilor (Fatick, Sénégal) - Daniel Gomis; Agnès Daba Thiaw-Benga; Aïssatou Sene; Aliou Guisse; Aminata Ndiaye (Physio-Géo)
The current climate crisis has pre-eminently become a planetary challenge to be met, leading the scientific community to question the contribution of plant ecosystems to this phenomenon through, among other things, studies of their carbon potential and monitoring of their evolution. With this in mind, the aim of this study was to diagnose the effect of land-use change on carbon stock flows in woody vegetation units in the Djilor district. To this end, a non-destructive approach based on allometric equations was adopted to estimate carbon stocks in each of these units from inventory data. Inventory data were collected randomly on square plots of varying sizes depending on the unit (10 by 10 m for mangroves, 20 by 20 m for savannah formations, 40 by 40 m for cultivated areas). The evolution of these units and their carbon stock was carried out using Landsat satellite images over the period from 1985 to 2017. The results revealed the carbon stocks of the different woody plant formations (5.2 tC.ha-1 for shrub savannah, 7.5 tC.ha-1 for cultivated areas, 10.2 tC.ha-1 for gallery forest, 11.7 tC.ha-1 for shrub to tree savannah, 22.7 tC.ha-1 for tree savannah and 25.3 tC.ha-1 for mangrove). Land-use changes over the 32-year period considered indicate a regressive dynamic for all spontaneous woody plant units, with degradation and deforestation outweighing conservation and restoration. The resulting reduction in carbon stock corresponds to an average annual global CO2 emission of around 11,5 kt. This study therefore shows the impact of land use changes on the carbon stocks of woody plant formations, and can serve as a basis of information for their monitoring and management.